2013
DOI: 10.1155/2013/260806
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Damage and Repair after Dry Needling in Mice

Abstract: Objective. Some dry needling treatments involve repetitive and rapid needle insertions into myofascial trigger points. This type of treatment causes muscle injury and can also damage nerve fibers. The aim of this study is to determine the injury caused by 15 repetitive punctures in the muscle and the intramuscular nerves in healthy mouse muscle and its ulterior regeneration. Methods. We repeatedly needled the levator auris longus muscle of mice, and then the muscles were processed with immunohistochemistry, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 33 publications
3
52
1
3
Order By: Relevance
“…32 It is likely that compared with acupuncture, TrP-DN could lead to more local microtrauma resulting in bruising, bleeding, and pain. 41 In the current study, however, no significant AEs were reported in 7629 treatments, giving an upper risk rate for significant AEs of #0.04%. 38 This compares favorably with 0.14% in the study by White et al 28 and 0.22% (AEs requiring further treatment) in the study by Witt et al 30 The estimated risk of significant AEs in this study (#0.04%) is also much lower than that reported for some over-the-counter pain medications (aspirin, 18.7%; ibuprofen, 13.7%; and Paracetamol, 14.5%).…”
Section: Discussioncontrasting
confidence: 57%
“…32 It is likely that compared with acupuncture, TrP-DN could lead to more local microtrauma resulting in bruising, bleeding, and pain. 41 In the current study, however, no significant AEs were reported in 7629 treatments, giving an upper risk rate for significant AEs of #0.04%. 38 This compares favorably with 0.14% in the study by White et al 28 and 0.22% (AEs requiring further treatment) in the study by Witt et al 30 The estimated risk of significant AEs in this study (#0.04%) is also much lower than that reported for some over-the-counter pain medications (aspirin, 18.7%; ibuprofen, 13.7%; and Paracetamol, 14.5%).…”
Section: Discussioncontrasting
confidence: 57%
“…9 It has been proven that multiple insertions of dry needling in the endplate zone of mice muscles cause a neuromuscular injury that mechanically damages muscle fibres and motor endplates. 42 There was complete regeneration in between three (neuromuscular injury) and seven (muscular injury) days. 42 It is conceivable that the precise location of the MTrP with the needle, confirmed by the LTR elicitation, could contribute to the destruction of the dysfunctional muscle fibres and motor endplates that cause the MTrP, accounting for the good results observed in the DDN group.…”
Section: Discussionmentioning
confidence: 96%
“…From this moment, the needle was reciprocated into the trigger point for 15 times with 1 Hz frequency and 1-2 cm along the vertical direction of the tissue [23] (without taking out the needle from the skin area). After the 15 th shot, the needle was remained in place for 5 minutes [15,17]. The patients were divided into two groups on the basis of the presence or absence of LTR during the reciprocating motion of the needle.…”
Section: Methodsmentioning
confidence: 99%
“…The patient's reports of "deqi" sensation were recorded [24,25]. The needle then remained in place for 5 minutes [15,17]. After 5 minutes, the needles were removed and the treatment site was disinfected again by alcohol-impregnated cotton.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation